Implementasi Penggunaan Teknologi Tubana dalam Mengatasi Permasalahan Sampah di Dusun Besuk Desa Curahmalang - Muliono, Muhamad; Maulana, Moch. Andri; Ubaidi, Ahmad Ragil; Dalimarta, Aris; Widodo, Moch. Heru (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The problem of household waste management in Besuk Hamlet, Curahmalang Village, is still dominated by open burning practices that cause air pollution, health problems, and environmental degradation. The limited waste management facilities encourage the need for alternative solutions that are simple, economical, and easy for the community to implement. This community service activity aims to implement TUBANA (Simple Waste Incinerator) technology as an effort to reduce pollution from waste burning while increasing public awareness and participation in more environmentally friendly waste management. The implementation method includes licensing stages, initial observation, socialization, design and construction of TUBANA through mutual cooperation, equipment trials, and education on the use and utilization of combustion ash. The results of the activity show that TUBANA is able to reduce smoke intensity compared to open burning, increase community knowledge and behavior change, and strengthen social aspects through active community participation. In addition, the ash from the combustion has the potential to be used as an ingredient in organic fertilizer, supporting the implementation of circular economy principles at the village level.